Interest of URS-L in the Treatment of Ureterolithiasis in Preschool Children - Halinski, Adam; Halinski, Andrzej; Zaniew, Marcin; Kudliński, Bartosz; Soltysiak, Jolanta; Sobolewski, Bartłomiej; Steyaert, Henri (Frontiers in Pediatrics, 2019)
Urolithiasis can affect all children aged 0 to 6 years. Diagnostic difficulties in the youngest children are due to the problems in locating pain and determining its character and severity. In keeping with the ALARA (As Low As Reasonably Achievable) protocol, the number of imaging tests possible to perform is very limited. Ultrasound is the first line exam of choice. After diagnosis of the presence of a stone, ESWL (Extracorporeal Shock Wave Lithotrypsy) should always be considered and offered to parents due to its high effectiveness and minimal invasiveness - especially for this age group. If ESWL is contraindicated or not well accepted by parents, the next therapeutic option is an endoscopic approach: URS-L (Uretherorenoscopy – Lithotrypsy). Our study clinically analyzes 87 children, which were treated between 2009-2017 using the URS-L procedure. URS-L treatments were performed using Lithoclast until 2009, and after that time, using the holmium laser Ho:YAG. The overall effectiveness of treatments was 93.3%. There was no failure in the access to the stones. A macroscopic hematuria (Clavien-Dindo I grade) was observed through the second post-operative day in 9.2% of treated patients. No urosepsis was observed. Full metabolic evaluation was performed on all patients. Children remained under constant urological and nephrological observation. A recurrence of urolithiasis was observed in 35.6% of the cases. Treating ureteral lithiasis in young infants remains a big challenge. Our series shows that modern minimal invasive techniques used by very experienced pediatric urologists in high volume centers gives excellent results. In most cases, surgery should no longer need to be an option.